Upregulation of MicroRNA‐107 induces proliferation in human gastric cancer cells by targeting the transcription factor FOXO1. Issue 4 (25th December 2013) - Li, Fan; Liu, Baohua; Gao, Yu; Liu, Yuliang; Xu, Yu; Tong, Weidong; Zhang, Anping
Abstract : MicroRNA‐107 (miR‐107) has been demonstrated to regulate proliferation and apoptosis in many types of cancers. Nevertheless, its biological function in gastric cancer remains largely unexplored. Here, we found that the expression level of miR‐107 was increased in gastric cancer in comparison with the adjacent normal tissues. The enforced expression of miR‐107 was able to promote cell proliferation in NCI‐N87 and AGS cells, while miR‐107 antisense oligonucleotides (antisense miR‐107) blocked cell proliferation. At the molecular level, our results further revealed that expression of FOXO1 was negatively regulated by miR‐107. Therefore, the data reported here demonstrate that miR‐107 is an important regulator in gastric cancer, which will contribute to a better understanding of the important mis‐regulated miRNAs in gastric cancer. Abstract : Correlation between miR‐107 expression levels and clinicopathological factors in patients with gastric cancer. Identification of miR‐107 as a transcriptional target of NF‐κB. Overexpression of miR‐107 promotes gastric cancer cell proliferation. miR‐107 regulates expression of cell‐cycle regulators, miR‐107 antisense reduces the proliferation of gastric cancer cells and miR‐107 negatively regulates FOXO1 expression in gastric cancer cells.